Stabilization of Caterpillar Shassis Hydropneumatic Suspension Parameters - A. J. Kotlobai; V. A. Korobkin; B. A. Lutskov; V. N. Kitchenco; A. A. Kotlobai (Наука и техника)
Parameters of ground clearance stabilization system for caterpillar chassis with hydro-pneumatic suspension of support rollers are substantiated. The paper contains description of ground clearance stabilization system, test results of the system being installed on a running caterpillar chassis model are cited